DUM-Tool - Romano, Simone; Scanniello, Giuseppe (ICSME : 2015 IEEE International Conference on Software Maintenance and Evolution : September 29, 2015-October 1, 2015, 2015)
With object-oriented programming languages (e.g., Java or C#), the identification of unreachable source code may be very complex especially when working at method level. To deal with the detection of unreachable methods, we have defined an approach named DUM: Detecting Unreachable Methods. We implemented a prototype of a supporting software we named DUM-Tool. It works on Java byte-code and detects unreachable methods by traversing a graph-based representation of a subject software.